Ascorbate and Alpha-Tocopherol Mitigate Toxic Pathological Changes in Adult Wistar Rats Exposed to Cypermethrin - Adeniyi, Temidayo Daniel; Moronkeji, Akinpelu; Ralph-Okhiria, Osetohanmen Flourish (Folia Medica Indonesiana, 2023)
The excessive and uncontrolled use of pyrethroids, such as cypermethrin (CP), for pest control in Nigeria could adversely affect humans. This study aimed to investigate the oxidative stress response to cypermethrin exposure, focusing on measuring the parameters (i.e., malondialdehyde (MDA), superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT)) and the potential therapeutic effects of single and co-administration of ascorbate and alpha-tocopherol. The lungs and hearts of the animals were histologically examined for cypermethrin-induced cytopathic changes. Twenty-five adult male Wistar rats weighing 180–200 g were randomly assigned to five groups, each consisting of five animals. Group I was the control group that was not subjected to any treatment. Group II was orally exposed to cypermethrin at a dosage of 10 mg/kg bw without any additional treatment. Groups III, IV, and V received cypermethrin at standard doses of 10 mg/kg bw and were orally administered with ascorbate (5,000 mg/kg bw), alpha-tocopherol (3,000 mg/kg bw), and a co-administration of ascorbate (5,000 mg/kg bw) and alpha-tocopherol (3,000 mg/kg bw), respectively. The animals were euthanized after 28 days, and samples were processed for histological analysis using hematoxylin and eosin staining. Analysis of variance (ANOVA) and Duncan's multiple range test were used to compare categorical variables of the biochemical parameters and determine the levels of MDA, SOD, GPx, and CAT. The data analysis revealed that the cypermethrin-exposed, untreated rats had elevated MDA levels and a concurrently marked decrease in SOD, GPx, and CAT activities (p<0.05). Additionally, the histopathological examination of the organs indicated inflammation and congestion. The co-administration of ascorbate and alpha-tocopherol restored the biochemical parameters more effectively compared to when the substances were administered individually. In conclusion, co-administration of ascorbic acid and alpha-tocopherol ameliorates cypermethrin-induced oxidative damage more effectively than a single administration of either substance. This may be due to the synergistic antioxidant properties of the substances.